Slope stability considering multi-fissure seepage under rainfall conditions - Jianqing Jia; Chengxin Mao; Victor O. Tenorio (Scientific Reports, 2024)
Abstract Fissures form the channel for rainwater infiltration, which accelerate the infiltration of rainwater into slope bodies, hence its important impact on the seepage field and stability of the slope. In this paper, taking one landslide of Liang-Wan freeway as the research object, firstly, the equivalent permeability coefficient method is used to homogenize the fissured soil. Then considering the boundary conditions of rainfall infiltration and groundwater level, a fluid–structure coupling model is established based on saturated–unsaturated seepage theory, and evolution characteristics of seepage, displacement and stress of the slope are studied. Based on these, the slope stability coefficient is determined. The results show that the rising rate of pore water pressure and volume water content of topsoil increases when multi-fissure seepage is considered, and the pore water velocity is larger in the local seepage range of fissures. With the increase of buried depth, the closer to groundwater level, the influence of multi-fissure seepage gradually weakens. The theoretical calculation results of slope displacement are more consistent with the field monitoring results. With the increase of rainfall time, the stability coefficient of slope decreases gradually, and the rate and range of decrease are greater.